A inclusão dos alunos surdos e/ou deficientes auditivos nas disciplinas do Centro de Ciências Exatas e Tecnologia da Universidade Federal de Sergipe - Fernandes, Priscila Dantas (2014)
Inclusion is to enter all students in regular education classes, seeking to respect and meet their social, cultural and educational needs. The aim of this study was to analyze the inclusion process of deaf and/or hearing impaired students in the subjects of Federal University of Sergipe (UFS), Centre for Exact Sciences and Technology, in São Cristóvão campus. It was intended to develop an analysis of the reality experienced by the students, their dynamics of studying, their difficulties and possible pedagogical and attitudinal barriers existing on campus. This research consists of a case study with qualitative and descriptive approach. As instruments for data collection, we used semi-structured interviews, document analysis and direct observations. We hope to contribute with suggestions to allow the improvement of deaf and/or hearing impaired students academic life within UFS, besides the process of teacher education in the higher level of education. We also seek to lead the scientific community to reflect on how the university still needs to make progress in inclusion. The results show misinformation and ignorance about deafness, lack of support from teachers, problems in teaching methodology, ignorance about sign language, lack of specific signs for Mathematics in Libras, attitudinal barriers, inadequate behavior of teachers in the classroom and bad structure of the university. Despite the flaws, the university presents significant progress, as the PAI/UFS Program, interpreters available, courses about inclusion, studies on this issue, and events on inclusive actions, among others.